Influence of strength training intensity of twice-a-week cycle on the immune status of athletes - Ясько [Gennady Yasko], Геннадій Володимирович (Slobozhanskyi Herald of Science and Sport, 2013)
<!--[if gte mso 9]> Normal 0 false false false RU X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> The justifications of the twice- intensity strength training exercises in a weekly cycle of physical education for students in higher education. As a material for immunological and biochemical studies of serum was taken. Calculated intensity of recommended load, which does not lead to the disruption of adaptation capabilities of the immune system and has a beneficial effect on health promotion students. Found that weight training threshold and middle level, held twice a week, are the most appropriate. Training sessions peak conducted with the same frequency may be undertaken only under the supervision of the sports doctor. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->